(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
According to weed distribution research outputs have been recorded 13 species belonging to 12 genera of 11 families in the wheat fields of Nart-1 center in Bornuursoum of Tuvaimag, among them, annuals for68.5%, biennials for 14.7% and perennials for 16.8% were estimated. The application of herbicides such as Penizan, Zinger, Lornet, Ovsygen express, Penizan + Ovsygen express and Zinger + Ovsygen for controlling both grassy and dicotyledonous weeds has Chenopodium album L, Polygonum convolvulus L, Paniciummiliaceum L, Avenafatua L, Setariaviridis L, Cannabis ruderalis, Fagopyrumtataricum L, Chenopodiumaristatum L, Salsolacollina (Pall), Amaranthusretro flexus L, SilenerepensPatr, Potentillabifurca L, Geranium siviricum L, Agropyronrepens L, Noneopulla L, C Linariaburiatica (Turcz), Potentillaanserina L, Artemisia sieversiana Willd, Plantago major L, Taraxacumofficinale Wigg, Medicagofalgate L were shown 87.5-100% technical effectiveness. Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 80-83